Influence of High Concentration of Silica Nanoparticles on the Dielectric Spectra - Soud, Ammar Al; Daradkeh, Samer; Knápek, Alexandr; Liedermann, Karel; Holcman, Vladimír; Sobola, Dinara (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2023)
In the presented work, we report the dielectricbehavior of epoxy–silicon oxide composites in the temperaturerange 240– 300 K, over the frequency range 10-2 Hz – 107 Hz. Themeasuring apparatus was based on the Novocontrol AlphaAnalyser and the measured data were analyzed and interpretedusing the Havriliak – Negami equation. The master curves of thereal part of permittivity and the dielectric loss number wereobtained by time–temperature superposition principle, and theresults showed that the nano-composite had a much higher lossfactor. Through the analysis of the origin of the dielectric responsein epoxy/silica composite, the reason for the different dielectricrelaxation behaviors of the nano-composite, and the pure epoxywas discussed.
Keywords: nanofillers; dielectric relaxation Spectroscopy,epoxy resin; nanocomposite